2001
DOI: 10.1097/00001786-200115020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Visitation in Critical Care: Processes and Outcomes of a Performance Improvement Initiative

Abstract: When family members became dissatisfied with a restrictive visiting policy in a combined coronary and medical intensive care unit, this situation was seen as an opportunity to better meet patient and family needs. A review of the literature indicated that open visitation policies enhance patient and family satisfaction, while a survey of patients, families, and health care team members revealed a desire for a more open visitation policy. Nursing staff, with input from other disciplines, developed and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 19 publications
1
53
0
4
Order By: Relevance
“…Although improved family satisfaction with less restrictive visitation policies is consistent with results of prior studies, 2,7,[10][11][12][13][14] improvement in the waiting room experience has not previously been demonstrated. One reason for the improved satisfaction may be that family members who spend less time in the waiting room may perceive it more favorably.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although improved family satisfaction with less restrictive visitation policies is consistent with results of prior studies, 2,7,[10][11][12][13][14] improvement in the waiting room experience has not previously been demonstrated. One reason for the improved satisfaction may be that family members who spend less time in the waiting room may perceive it more favorably.…”
Section: Discussionsupporting
confidence: 79%
“…Patient and staff safety, staff workload, patient privacy, and adverse changes in patients' physiology have all been cited as concerns related to open visitation. 7,9,10 Numerous studies have demonstrated that liberalization of visitation hours can lead to improved satisfaction of patients' families, [10][11][12][13][14] patients, 12,14,15 and nurses 10,11,12 without adverse effects on clinical outcomes. Some studies have even demonstrated that family visitation can lead to improved cardiovascular outcomes for patients.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Families form the fundamental unit of a person's life and function as a team to support the person psychologically, ethically, socially, and spiritually. 8,[10][11][12][13] The burden of pain and disease of one family member will somehow overshadow the well-being of the whole family. 9,14 Negative intense reactions, such as anger, irritability, shock, grief, and loss of control are often prevalent outside the ICUs, creating the need for closeness for family members to stay by the bedside of their beloved.…”
Section: Survey Development and Testingmentioning
confidence: 99%
“…Research data 12,22,[31][32][33][34][35][36] on nurses' visitation preferences and satisfaction differ among countries and facilities. Current visiting practices also vary internationally, from closed ICUs to free visiting during the day, indicating that this topic is still controversial.…”
mentioning
confidence: 99%
“…5 Some evidence indicates that family members want to perform some patient care such as touching, encouraging, and assisting with daily living routines. 6,7 …”
mentioning
confidence: 99%